Characterization of Modified PVDF Membranes Using Fourier Transform Infrared and Raman Microscopy and Infrared Nanoimaging: Challenges and Advantages of Individual Methods - Kmetík, Matěj; Kopal, Ivan; Král, Martin; Dendisová, Marcela (ACS omega, 2024)
Polymer materials are integral to diverse scientific fields, including chemical engineering and biochemical research, as well as analytical and physical chemistry. This study focuses on the characterization of modified poly(vinylidene fluoride) (PVDF) membranes from both physical and chemical perspectives. Unfortunately, current surface characterization methods face various challenges when simultaneously measuring diverse material properties such as morphology and chemical composition. Addressing this issue, we introduce infrared scattering scanning near-field optical microscopy (IR-sSNOM), a modern technique with the ability to overcome limitations and provide simultaneous topographical, mechanical, and chemical information. We demonstrate the capabilities of IR-sSNOM for investigation of four samples of PVDF membranes modified with 2-(methacryloyloxyethyl)trimethylammonium iodide and/or methacryloyloxyethyl phosphorylcholine in various ratios. These membranes, desirable for their specific properties, represent a challenging material for analysis due to their thermal instability and mechanical vulnerability. Employing Fourier transform infrared (FTIR) microscopy, IR-sSNOM, and Raman microscopy, we successfully overcame these challenges by carefully selecting the experimental parameters and performing detailed characterization of the polymer samples. Valuable insights into morphological and chemical homogeneity, the abundance of modifying side chains, and the distribution of different crystal phases of PVDF were obtained. Most notably, the presence of modifying side chains was confirmed by FTIR microscopy, the Raman spectral mapping revealed the distribution of crystalline phases of the studied polymer, and the IR-sSNOM showed the abundance of chemically diverse aggregates on the surface of the membranes, thanks to the unique nanometer-scale resolution and chemical sensitivity of this technique. This comprehensive approach represents a powerful toolset for characterization of polymeric materials at the nano- and microscale. We believe that this methodology can be applied to similar samples, provided that their thermal stability is considered, opening avenues for detailed exploration of physical and chemical properties in various scientific applications.